Physico-Chemical Analysis of a Herbal Classical Formulation-Shleshmatakadhya Agada Ghanvati - Vanya Gupta; Ved Bhushan Sharma; R. C. Tiwari; Om Prakash Gupta (AYUSHDHARA, 2022)
One of India's ancient systems of medicine is Ayurveda. The fundamental principal of Ayurvedic medicine is to keep your body, mind, and environment in balance and harmony in order to prevent and treat sickness rather than to treat symptoms of disease. In order to treat the disease's underlying cause and restore balance, Ayurveda uses natural ingredients. For a very long period, herbal medicines were used for a variety of therapeutic goals in ancient Chinese, Greek, Egyptian, and Indian medicine. According to the World Health Organization, 80% of the world's population still primarily relies on traditional medicines for their medical care. With around 45,000 plant species, the Indian subcontinent is renowned for being one of the key hubs for biodiversity. Sharangdhara Samhita, emphasised the idea of polyherbalism as a means of enhancing therapeutic efficacy. Sometimes the active phytochemical components of a single plant are not enough to bring about the intended therapeutic results so they are mixed in a certain ratio to enhance the therapeutic effects and combat toxicity. Hence new findings in Ayurveda are gradually focusing on the significance of poly herbalism and its clinical relevance. In this study, efforts have been made to lay down analytical standards for Shleshmatakadhya Agada Ghanavati, which were not found reported till date. Shleshmatakadhya Agada Ghanavati was manufactured at the Hans Herbal Pvt. Ltd. Pharmacy, Haridwar were within acceptable range. Determination of heavy metals was also done additionally and the result showed that all the metals were within the API limits in the formulation. In TLC, 3 spots were found.